Respuesta :

bobeld
Let's get the same terms on the same side.
I am going to remove 5x from both sides of the equation by subtracting 5x

5x - 5x -7 = 7x -5x - 17
           -7 = 2x - 17   now lets remove the 17 from both sides
       -7 + 17 = 2x     (why do we add 17?  Think of 2x -17 as 2x +  -17.  Tor remove a negative number we add it.
Now we finally have     10=2x and if we divide both sides by 2

10  = 2x
2       2    we get that x = 5
Let's check by substituting 5 in the original equation:
5(5) - 7 = 7(5) - 17
25 - 7 = 35 - 17
18      =       18